BOBOT OVARIUM DAN HIRARKI FOLIKEL OVARIUM PUYUH JEPANG (COTURNIX COTURNIX JAPONICA) SETELAH PENCAHAYAAN DENGAN CAHAYA MONOKROMATIK - Lukman Hakim; Koen Praseno; Tyas Rini Saraswati (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2014)
Light has an important role in the avian life. Illumination can control any physiological process including reproduction and egg production because hormonal system is regulated by the light. One of the ways to optimize egg production is by optimizing management of lighting system including monochromatic lighting. The present study was designed to know potension of monochromatic light green, red, and blue with intensities of 5 lux for 12 hours daily to increase weight of ovary and number of ovary follicles in the quail. Quails divided to 4 groups and 5 repititions. The treatments were controls treatment used incandescent bulb with 5 W, second treatment used red lights with 5 W, third treatment used green lights with 5 W, fourth treatment used blue lights with 5 W. The red, green, and blue lights were provided by light emitting diodes (LED). Parameters measured were weight of ovary, number of ovary follicles, weight of body, food consumption, and water consumption. Data was analysed with Analysis of Varian (ANOVA) and Duncan Analysis in 95% significant. The result showed that there are significant different in weight of ovary, weight of body, and food consumption. Monochromatic light is more effective to increase weight of ovary, weight of body, decrease food consumption than fluorescant lamp. The Summary is monochromatic light can be used in management of lighting alternative in quail cultivation to optimyze quail production. Keywords : Weight Of Ovary, Monochromatic Light, Number Of Ovary Follicles, Quail.